Effects of Different Training Interventions on the Recovery of Physical and Neuromuscular Performance After a Soccer Match. Issue 8 (August 2020) - Trecroci, Athos; Porcelli, Simone; Perri, Enrico; Pedrali, Magda; Rasica, Letizia; Alberti, Giampietro; Longo, Stefano; Iaia, F. Marcello
Abstract : Abstract: Trecroci, A, Porcelli, S, Perri, E, Pedrali, M, Rasica, L, Alberti, G, Longo, S, and Iaia, FM. Effects of different training interventions on the recovery of physical and neuromuscular performance after a soccer match. J Strength Cond Res 34(8): 2189–2196, 2020—In competitive soccer, players are frequently required to play in periods with congested fixtures in which they have limited time to recover between matches (3–4 days). Thus, finding the most appropriate intervention strategy to limit players' neuromuscular (muscle function of lower limbs) and physical (running performance) impairments in this short period becomes crucial. The aim of the study was to examine how muscle function of knee extensors and flexors and sprint performance recovered +72 hours after match in relation to different field-based training sessions. Using a crossover design, 9 subelite players (age 17.6 ± 0.5 years, height 1.77 ± 0.02 m, body mass 66.4 ± 5.8 kg) underwent a soccer-specific training (SST) session or an active recovery regime (AR) on the second day after a match. Immediately after (0 hour) and +72 hours after match, 30-m sprint and repeated sprint ability (RSA) were assessed. Maximum isometric voluntary force (MVF) of knee extensors and flexors was determined at 120° and 90° (with 180° being full extension), respectively. SST and AR promoted similar effects on the recovery kinetics of sprint, RSA, and MVF of knee extensors ( p > 0.05). However, compared with SST, AR promoted a significantly better restoration of MVF of knee flexors ( p < 0.05) after +72 hours from the match. Because muscle fatigue has been related with increased hamstring injury risk, a training based on AR can be a valid intervention to promote the recovery of muscle force production of knee flexors and reduce hamstring injury risk in the postmatch period.